Experimental in vivo studies of the antitumor efficacy of photodynamic and radiodynamic therapy and their combinations - D. A. Tzerkovsky; D. A. Kozlovsky; A. N. Mazurenko; N. D. Adamenko; F. F. Borichevsky (Biomedical Photonics, 2023)
The authors studied the antitumor efficacy of photodynamic therapy (PDT) in combination with radiodynamic therapy (RDT) in an in vivo experiment. The study was approved by the Ethics Committee of the N.N. Alexandrov National Cancer Center of Belarus (protocol dated February 25, 2022, № 180). The work was performed on 26 white non-linear rats weighing 200 ± 50 g. Pliss lymphosarcoma (PLS) was used as a tumor model, which was transplanted subcutaneously. Photosensitizer (PS) «Photolon» (RUE «Belmedpreparaty», Belarus) was administered intravenously at a dose of 2.5 mg/kg of body weight. The RDT session was performed by the contact method (CRT) once 2.5–3 times after the end of the infusion of the PS on the «microSelectron-HDR V3 Digital apparatus» (Elekta, Sweden) using γ-radiation (192Ir) in a single focal dose 6 Gy. A PDT session was performed once immediately after exposure to ionizing radiation using a «PDT diode laser» (LTD Imaf Axicon, Belarus, λ=660±5 nm) at an exposure dose of 100 J/cm2  with a power density of 0.2 W/cm2  and a power of 0.353 watts. All rats were divided into 4 groups of 6–7 animals each: intact control (IC), PS + PDT, PS + CRT, PS + CRT + PDT. The criteria for evaluating antitumor efficacy were: the average volume of tumors (Vav, cm3 ), the coefficient of absolute growth of tumors (K, in RU), the coefficient of tumor growth inhibition (TGI, %), the frequency of complete tumor regressions (CR, %), the proportion of cured rats (%), an increase in the average duration of dead rats (%). Differences were considered statistically significant at p<0.05. On the 18th day of the experiment, Vav. in groups was 63.25±2.76 cm³; 29.03±6.06 cm³ (p=0.0002); 22.18±5.94 cm³ (р<0.0001); 11.76±3.29 cm³ (p=0.0000), respectively. Coefficients K – 4516.86 RU; 2638.09 RU; 2024.45 RU; 979.00 RU. TGI coefficients – 54.10% (PS + PDT); 64.93% (PS + CRT); 81.41% (PS + CRT + PDT). An increase in the average duration of dead rats indicator – 48.57% (PS + PDT); 60.00% (PS + CRT); 97.71% (PS + CRT + PDT). On the 60th and 90th days of the experiment, the frequency of PR and the proportion of cured rats were the same and amounted to 0%; 16.7%; 14.3%, and 28.6%, respectively. The results obtained indicate the prospects and relevance of further research in this scientific direction.